IMPROVING STUDENT LEARNING MOTIVATION FOR TRADITIONAL BOLA ASTI SPORTS LEARNING IN CLASS VII OF SMP NEGERI 13 BANDA ACEH - Andelina febriani; Azrul Ridwan; Ruslan; Mansur (Journal of Quality Islamic Education Research, 2025)
This study aims to improve students' learning motivation in traditional sports learning bola asti in class VII of SMP Negeri 13 Banda Aceh. The problem faced is the low motivation of students in participating in traditional sports learning, especially bola asti, which affects skills and learning outcomes that are not optimal. For this reason, Classroom Action Research (CAR) with a cycle design is used as a research approach, which consists of four main stages: planning, implementation, observation, and reflection. The subjects of this study were 30 students in class VII consisting of 15 male students and 15 female students. The instruments used in data collection included observations of student activities, motivation questionnaires to measure student motivation levels, and interviews to dig deeper into students' perceptions of traditional sports learning. The results of the study showed a significant increase in student learning motivation in each cycle carried out. In the first cycle, although students began to show interest in the bola asti game, learning motivation was still relatively low. However, in the second cycle, with the implementation of more interesting learning strategies, such as providing more intensive feedback and more varied game techniques, student motivation increased quite significantly.